Keeping your cool in extreme conditions: Strategies to maximise performance - Laursen, P. (Science + Triathlon 2015 World Conference, 2015)
Exercising in hot conditions increases the storage of heat in the body, as shown by the rise in core temperature. Thermoreceptors located throughout the body detect the thermal change, and relay this information to the brain, creating a subconscious lowering of motor output. This response lowers the rate of heat production from the contracting skeletal muscles to minimize possible thermal injury, but performance is also reduced (Racinais et al., 2015). Another response and defense to the rise in body temperature is the production of sweat, which creates a powerful cooling mechanism for heat loss in hot-dry climates, but is less effective in hot-humid climates. Accordingly, past strategies to counteract the considerable fluid losses that arise during competition has been a primary focus, with governing bodies and position stands recommending athletes drink to prevent body mass losses to no greater than 2%. However more recent data suggests that a more appropriate strategy to maximize performance is to simply follow the inbuilt mechanisms driving water balance in the body, namely by drinking to the dictates of thirst (Cotter et al., 2014). From an applied perspective, it has been found that performance in the heat is most effectively enhanced with aerobic fitness development and heat acclimation (Racinais et al., 2015). However, two acute methods that increase performance in the heat involve a focus on counteracting the bodily reactions to heat development and include pre-exercise cooling and consuming cold fluids during exercise. Pre-cooling involves the lowering of core body temperature, or the thermal state of the body, prior to competing in the heat, and can be administered externally, with cold-water immersion or iced garments, or internally, through the ingestion of cold fluids (Siegel & Laursen, 2012). Cold fluid ingestion during prolonged exercise in the heat can lower core temperature, as well as the perception of the body`s thermal state, and exercise performance is enhanced (Burdon et al., 2013). A beverage formation with high cooling capacity is ice slurry, which is a mixture of water, ice, and sugar/ electrolytes. Ingesting ice slurry has been shown to lower core temperature prior to exercise, and is considered a practical strategy for use in warm conditions, as it also provides fluids to replace lost water from sweating (Siegel & Laursen, 2012). In summary, strategies for maximizing performance in extreme conditions include the development of aerobic fitness through training, heat acclimatization, pre-exercise cooling that is practical, and drinking cold fluid and ice slushy drinks before and during exercise according to the dictates of thirst and at appropriately strategic times.